PEMODELAN APLIKASI PENDUKUNG KEPUTUSAN MAKANAN PENDAMPING AIR SUSU IBU (MPASI) BERBASIS ANDROID - Rabby Nazli; Erlinda Erlinda (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2020)
Complementary foods breast milk (MPASI) is a very important thing for growth and development in a baby, to achieve optimal growth and development process, balanced nutrition is needed, even nowadays babies are often stunted or have malnutrition. Good parents, of course, do not just provide complementary foods to their babies but will pay attention to whether or not the MPASI nutrition is given. By modeling an MPASI guide application, it can help parents determine the right nutrition to give to their babies and parents can make the right decisions and find out the nutritional status of their babies. Modeling this application using Unifield Modeling Language (UML) and implemented into the application using Android Studio. From the resulting application model, it can help and provide references to parents in providing balanced nutrition for their babies.